Respuesta :

GK0613

Answer:

no solution

Step-by-step explanation:

2(x-3)=2x+3

2x-6=2x+3

-2x.  -2x

-6=3

Answer:

There is no solution.

Step-by-step explanation:

1) DIstribute 2(x - 3), you should receive 2x - 6.

2) Set 2x - 6 equal to 2x + 3, so (2x - 6 = 2x + 3).

3) Add 6 to both sides (inverse of -6), which cancels the negative 6 (-6) on the left out, and causes the positive 3 (+3) on the right side to become positive 9 (+9).

4) Subtract 2x from both sides (inverse of 2x), which causes both of the 2x's to cancel out.

5) The equation becomes 0 = 9 which is not correct, and false.

The result is that there is no solution to this equation.

ACCESS MORE